Do we need new trials of procalcitonin-guided antibiotic therapy? - Lisboa, Thiago (2018)
Funding Information: Publication was funded by Rede Institucional de Pesquisa e Inovação em Medicina Intensiva (RIPIMI), Complexo Hospitalar Santa Casa de Misericordia de Porto Alegre. Publisher Copyright: © 2018 The Author(s).